The Impact of Sleep Quality on Cognitive Function in Community-Dwelling Older Adults - Mahjoobeh Betyar; Farzan Kheirkhah; Seyed Reza Hosseini; Ali Bijani; Sussan Moudi (Elderly Health Journal, 2023)
Introduction: Given the high prevalence of poor sleep quality in late adulthood, older adults might be involved with different physical, mental and social consequences of this disorder. Current research was conducted to examine the association between sleep quality and cognitive function in community-dwelling older adults. Methods: This cross-sectional study was carried out on 800 community-dwelling people aged ≥ 60 years living in Amirkola, North of Iran. The participants were selected by simple random sampling method. Mini-Mental State Examination, and the Pittsburgh Sleep Quality Index (PSQI) were used for data collection. Seven components of the sleep quality were categorized into the four groups (very good, relatively good, relatively poor, and very poor condition). The participants were divided into the two groups based on their cognitive function, and sleep quality was compared between these two groups. Mann-Whitney, Spearman's correlation analysis, Chi-square, Pearson's correlation test and Logistic regression analysis were used to analyze the collected data. Results: Mean PSQI score among the older adults with normal and abnormal cognitive function was 5.5 ± 3.2 and 5.8 ± 3.3, respectively (p = 0.508). Poor sleep quality was slightly more prevalent in the elderly with cognitive dysfunction (p = 0.775). Logistic regression analysis revealed age (adjusted OR = 1.06; 95% CI: 1.03-1.08; p < 0.001) and level of education (adjusted OR = 0.14; 95% CI: 0.09-0.20; p < 0.001) had a significant impact on cognitive function; PSQI score (p = 0.254), gender (p = 0.661), and administration of sleeping drugs  showed no significant effect (p = 0.081). Conclusion: Among different components of sleep quality, a significant positive association was observed between the frequency of sleep disturbances with cognitive function in older adults; furthermore, older age and lower level of education showed a significant negative effect on cognitive function.